ANALISIS PENGGUNAAN APLIKASI MOKA POS DALAM SISTEM INFORMASI PENERIMAAN KAS (STUDI KASUS UMKM AAB DI KECAMATAN CIPARAY): Use of the Moka POS Application - Trisusena, Bambang; Marisa Nur Diyani, Asri; Fransisca, Anggie; Gunardi, Gunardi (Jurnal Teknologi Komputer dan Informatika, 2023)
Point of Sale (POS) applications such as Moka POS have become an important aspect in managing cash receipt systems in various types of businesses. This research presents a general overview of the use of the Moka POS application in the context of cash receipts management. Moka POS not only simplifies the sales transaction process, but also provides various features that support financial management and business operations.Data was gathered in October 2023 and results were reached using a qualitative descriptive approach. Primary data from cashiers and AAB MSME owners were directly gathered for this study, along with secondary data from journals, e-books, and Mendeley. Three techniques were employed to acquire the data: observations, interviews, and documentation studies. According to study results, beginning January 2021, AAB MSMEs have operated cashier operations more effectively because the Moka Pos application was integrated into the cash receiving system.